UPDATING APPLE CHLOROTIC LEAF SPOT VIRUS (ACLSV) STATUS OF SWEET CHERRY IN BULGARIA - Borisova, Aneliya (Journal of Agricultural Sciences (Belgrade), 2024)
Sweet cherry (Prunus avium L.) is one of the most important stone fruit species in Bulgaria. Cherry is susceptible to many viruses to gather better insight into the phyto-virologic status of sweet cherry, outside the Ilarviruses, a survey was carried out for the presence of apple chlorotic leaf spot virus (ACLSV), cherry leafroll virus (CLRVR), and raspberry ringspot virus (RpRSV) in 32 commercial and 6 collection orchards in ten regions in Bulgaria, between 2017–2022. In total 1503 sweet cherry samples were collected from symptomatic trees as well as from symptomless ones. These samples were tested by Cocktail ELISA for ACLSV and DAS-ELISA for CLRVR, RpRSV аnd additionally for prune dwarf virus (PDV) and prunus necrotic ringspot virus (PNRSV) in order to establish mixed infections. From all three assessed viruses (ACLSV, CLRSV, and RpRSV) only ACLSV was detected in commercial and collection sweet cherry orchards in all regions with intensive cherry cultivation in Bulgaria. The level of ACLSV virus infection was 8.8%. The most frequent was single ACLSV infection representing 79.6% of infected sweet cherry trees, followed by ACLSV and PDV (14.4%) and the lowest one was ACLSV and PNRSV (6.0%). The presence of ACLSV in orchards of different ages, including ‘young’ ones, indicated the need to use virus-free propagating material when establishing new fruit orchards to prevent the spread of pathogens with planting material.